بصيرة اللغة: نظرة براجماتية Book Chapter ” حان وقت حرية التعلم “ تأليف نينو إندريانتو والأصدقاء - Dina Putri Juni Astuti; Ikke Wulandari (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
Language wisdom is a language unit selection strategy that is used to become a filter in dealing with language communication in terms of pragmatics in the digital era 4.0. The strategy for selecting language units in this study is based on the classification of speech acts and the principles of politeness in language used in vocabulary in the book chapter “Time for Freedom to Learn” by Nino Indrianto et al. The research method used is descriptive method with data collection techniques using library research techniques. Where the research data is in the form of sentences related to language wisdom with a pragmatic review of the book chapter "Time for Freedom to Learn" section of Language Learning and the source of data in this study is the book chapter "Time for Freedom to Learn" by Nino Indrianto et al. Published by Akademia Pustaka, Tulungagung in 2021, the first printing with a total of 238 pages. The results of this study indicate that there is a link between language wisdom in terms of pragmatics, where the strategy for selecting language units is seen from two aspects, namely the classification of speech acts and the principle of politeness. From the findings of the research, the percentage of speech act classification that is more dominant is derived from directives, with the highest percentage being 58.3% in the second text. Where the directive is a form of speech act that makes the speech partner do something on what is recommended by the speaker. Thus, the second text conveys more positive suggestions or recommendations in an effort to improve language learning. While in terms of politeness principles, it can be concluded that the maxim that often appears in the data text is the side of generosity, with a percentage of 34.69%. Where the reader shows more good nature, generosity, good character, and good character.